GHRELIN, NITRITE AND PARAOXONASE/ARYLESTERASE CONCENTRATIONS IN CEMENT PLANT WORKERS - Aydin, Suleyman; Aydin, Suna; Croteau, Gerry A.; Sahin, Ibrahim; Citil, Cihan (Sciendo, 2010)
Occupational cement dust exposure has been associated with an increased risk of liver abnormalities, pulmonary disorders, and carcinogenesis. Decreased antioxidant capacity and increased plasma lipid peroxidation have been posed as possible causal mechanisms of disease. Accordingly, this study examined the serum paraoxonase (PON1) arylesterase (AE), ghrelin, HDL-C, LDL-C and serum nitrite (NOx) levels in cement dust exposed workers. Twenty-eight volunteer male cement plant workers and 30 volunteer control male workers, aged 29-54 years, participated. The concentrations of serum PON1, AE, NOx, ghrelin, and HDL-cholesterol and LDL-cholesterol were measured in both groups. PON-1, AE, ghrelin and HDL-cholesterol were lower in the cement plant workers than in controls. Serum nitrite (NOx), and LDL-C levels in cement plant workers were higher (p<0.05) than in the control group workers. No correlation was observed between the serum levels of HDL-cholesterol and PON1 and between HDL-cholesterol and ghrelin. A weak negative correlation was detected between the serum ghrelin and NOx. The study results strongly suggest that HDL paraoxonase, AE, ghrelin, HDL-C, and high NOx, and LDL-C levels may have a role in disease involving oxidative damage. However, some studies are necessary to address the association between occupational dust exposure and respiratory symptoms.
Keywords: cement dust; occupational exposure; paraoxonase; nitrite; ghrelin